PENGARUH PEMBERIAN PAKAN ORGANIK NT45 SERI I TERHADAP PERTUMBUHAN BIBIT IKAN PATIN JAMBAL (Pangasius djambal) - Rizki, Zaidan; Razak, Abdul; Widiana, Rina (Pendidikan Biologi, 2013)
ABSTRACTÂ Freshwater fish farming has become an indispensable agribusiness activities with fishmeal industry, one of which Jambal Catfish ( Pangasius djambal ). Feed the fish that have been used so far by ranchers/farmers, known as fish pellets. Feed pellet mill is easy to come by, but the feed pellets can damage the environment, because it can lead to water pollution. Additionally pellet prices continue to rise each year. In contrast to the NT45 Organic food contains bacteria that can clean water penggurai of turbidity and can fertilize with water triggers the Planton. Organic feed NT45 Series I also do not use synthetic chemicals and does not contain toxins and the price is also cheaper. Based on the background above, has done research on The Effect of Organic Feed NT45 Series I on growth of seedlings Jambal Catfish (Pangasius djambal). The purpose of this study was to observe the effect of feeding organic NT45 Series I on the growth of seedlings jambal catfish (Pangasius djambal). This study was conducted in February and March, 2013, housed in the Department of Biology FIMPA Ecology Laboratory, State University of West Sumatra Padang. This study is an experimental study. This study was designed with RAL (completely randomized design) with 4 treatments and 6 replications. The sample in this study is Jambal Catfish (Pangasius djambal) aged 8 weeks. The parameters measured were the length of the total, the length and weight of fish standards. Data analysis was performed with Variety Analysis and Test followed by Least Significant Difference (LSD) at Î± 5 %. The results showed that the organic feed NT45 Series I have a positive influence on the growth of seedlings Jambal Catfish (Pangasius djambal) both the length of the fishs body and the body weight gain Jambal Patin. Organic feed number NT45 Series I best to improve weight and body length Catfish Jambal is 3.78 g/day.Â